DIAGNOSTIC ACCURACY OF DOPPLER RESISTIVE INDEX IN DIFFERENTIATING MALIGNANT FROM BENIGN THYROID NODULES TAKING HISTOPATHOLOGY AS GOLD STANDARD (Journal of Medical & Health Sciences Review, 2025)
Background: Thyroid nodules are common, with some risk of malignancy. FNAC is the standard diagnostic tool but has limitations. Doppler Resistive Index (RI) offers a non-invasive alternative. This study assesses its accuracy using histopathology as the gold standard.Materials and Methods: This cross-sectional study, conducted at the Punjab Institute of Neurosciences, Lahore (August–December 2024), included 111 grayscale ultrasound-confirmed thyroid nodule patients. Non-probability consecutive sampling was used. Resistive Index (RI) was measured from the nodule. Nodules with RI ≤ 0.7 were benign, while RI ≥ 0.71 indicated malignancy. SPSS version 22 analyzed sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall diagnostic accuracy.Results: Among 111 patients, 31.5% were male and 68.5% female. The mean age was 49.68 ± 7.14 years, lower in malignant cases (46.86). Malignant cases also had a lower BMI (18.46 vs. 23.42). Mean RI was higher in malignant (0.77) than benign nodules (0.56). DDUS showed 81.1% sensitivity, 89.2% specificity, 78.9% PPV, and 94.5% NPV for malignancy detection. The ROC curve yielded an AUC of 0.955, indicating excellent accuracy.Conclusion: Doppler Resistive Index (RI) accurately differentiates malignant from benign thyroid nodules. It serves as a non-invasive, cost-effective FNAC adjunct, especially in resource-limited settings.